Object repetition leads to local increases in the temporal coordination of neural responses - Gilbert, Jessica R.; Gotts, Stephen J.; Carver, Frederick W.; Martin, Alex (Frontiers in Human Neuroscience, 2010)
Experience with visual objects leads to later improvements in identification speed and accuracy ("repetition priming"), but generally leads to reductions in neural activity in single-cell recording studies in animals and fMRI studies in humans. Here we use event-related, source-localized MEG (ER-SAM) to evaluate the possibility that neural activity changes related to priming in occipital, temporal, and prefrontal cortex correspond to more temporally coordinated and synchronized activity, reflected in local increases in the amplitude of low-frequency activity fluctuations (i.e. evoked power) that are time-locked to stimulus onset. Subjects (N=17) identified pictures of objects that were either novel or repeated during the session. Tests in two separate low-frequency bands (theta/alpha: 5-15 Hz; beta: 15-35 Hz) revealed increases in evoked power (5-15 Hz) for repeated stimuli in the right fusiform gyrus, with the earliest significant increases observed 100-200 ms after stimulus onset. Increases with stimulus repetition were also observed in striate/extrastriate cortex (15-35 Hz) by 200-300 ms post-stimulus, along with a trend for a similar pattern in right lateral prefrontal cortex (5-15 Hz). Our results suggest that experience-dependent reductions in neural activity may affect improved behavioral identification through more coordinated, synchronized activity at low frequencies, constituting a mechanism for more efficient neural processing with experience.